Effects of Zr and Ga doping on the stoichiometry and properties of niobium oxides. Issue 1 (January 2016) - Nico, C.; Soares, M.R.N.; Costa, L.C.; Monteiro, T.; Graça, M.P.F.
Abstract: During the last two decades, niobium based materials have received much attention due to their properties and potential applications. It is known that Nb forms several stable oxide crystal structures: NbO (electrical conductor), NbO2 and Nb2 O5 (insulators), but also non-stoichiometric phases. In this work, in order to understand the effect of doping on the dielectric constant, niobium oxides pellets doped with different concentrations of ZrO2 and Ga2 O3 were prepared and heat-treated at temperatures between 300 and 1100 °C. The XRD patterns have shown that the increase of the heat-treating temperature promotes the structural transformation from cubic to orthorhombic and then to monoclinic. A Raman spectroscopy analysis helped to complement the structural information of the doped niobium oxides. It was observed that the presence of the doping agents promotes the crystallization of the Nb12 O29 monoclinic phases at the highest temperatures. The samples were also characterized using optical absorption and impedance spectroscopy. The influence of the morphology (analysed by SEM) and structural characteristics on the dielectric properties, at room temperature and in the frequency range 40 Hz to 2 MHz is discussed and reported. Overall, this work shows the effect of doping agents in niobium oxides, particularly on their structure and stoichiometry. These properties are of extreme relevance for the development of resistive random access memories (RRAM), where oxygen vacancies play a central role, but they are also an important issue regarding a better understanding of the synthesis of different niobate systems, such as alkali niobates.